2005
DOI: 10.1074/jbc.m411141200
|View full text |Cite
|
Sign up to set email alerts
|

Different from the HIV Fusion Inhibitor C34, the Anti-HIV Drug Fuzeon (T-20) Inhibits HIV-1 Entry by Targeting Multiple Sites in gp41 and gp120

Abstract: Fuzeon (also known as T-20 or enfuvirtide), one of the C-peptides derived from the HIV-1 envelope glycoprotein transmembrane subunit gp41 C-terminal heptad repeat (CHR) region, is the first member of a new class of anti-HIV drugs known as HIV fusion inhibitors. It has been widely believed that T-20 shares the same mechanism of action with C34, another C-peptide. The C34 is known to compete with the CHR of gp41 to form a stable 6-helix bundle (6-HB) with the gp41 N-terminal heptad repeat (NHR) and prevent the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
235
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 211 publications
(262 citation statements)
references
References 64 publications
24
235
3
Order By: Relevance
“…33,000°cm 2 dmol Ϫ1 ) according to previous studies (4,20). Thermal denaturation of the samples was monitored at 222 nm by applying a temperature gradient from 20°C to 98°C with a 2-degree interval, an equilibration time of 1.5 min, and an averaging time of 60 s. The midpoint of the thermal unfolding transition (T m ) values was calculated using Jasco software utilities as described previously (21).…”
Section: Methodsmentioning
confidence: 99%
“…33,000°cm 2 dmol Ϫ1 ) according to previous studies (4,20). Thermal denaturation of the samples was monitored at 222 nm by applying a temperature gradient from 20°C to 98°C with a 2-degree interval, an equilibration time of 1.5 min, and an averaging time of 60 s. The midpoint of the thermal unfolding transition (T m ) values was calculated using Jasco software utilities as described previously (21).…”
Section: Methodsmentioning
confidence: 99%
“…M36 and scFv m9 did not neutralize the clade E isolate GXE at concentrations up to 667 nM. M36 was also on average more potent than the peptide C34 (Table 1); C34 (10) is a gp41-derived peptide that exhibits HIV-1 entry inhibitory activity comparable to or higher than that of the FDA approved peptide entry inhibitor T20 (DP178, brand name Fuzeon), which shares significant sequence homology with C34 although inhibits entry by a somewhat different mechanism involving binding to multiple sites (11). The inhibitory activity of m36 was dose dependent (Fig.…”
mentioning
confidence: 99%
“…While previous research concluded that HR-1 peptides could be effective inhibitors of type I integral membrane fusion proteins when constrained and presented as trimeric helical bundles (8,28), our data suggest that individual HR-1 peptides can lead to effective viral inhibition. Furthermore, recent studies of HR-2 peptides suggest the potential for multiple viral targets for inhibitory peptides (20). The prophylactic nature of the HR-1 peptide could be explained by interaction with additional targets or strong binding to the metastable prefusion state of the F protein, possibly preventing stalk extension.…”
Section: Discussionmentioning
confidence: 99%